On completeness of quasi-pseudometric spaces - Seithuti P. Moshokoa (International Journal of Mathematics and Mathematical Sciences)
We discuss completeness in terms of a notion of absolute closure. This will be done in the context of separated quasi-pseudometric spaces and bitopological spaces. The notion is equivalent to the classical notion of completeness when restricted to the class of metric spaces.